2020
DOI: 10.1016/j.jpain.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mu-Delta Opioid Agonist Demonstrates Enhanced Efficacy With Reduced Tolerance and Dependence in Mouse Neuropathic Pain Models

Abstract: A novel mu-delta opioid agonist demonstrates enhanced efficacy with reduced tolerance and dependence in mouse neuropathic pain models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…This was not noticed for 14-OMO (3) vs. 3a, and 14-MM (4) vs. 4a, indicating that an increased µOR affinity can be achieved by either a 14-methoxy or by an N-phenethyl substitution, as key sites to be targeted in modulating the binding affinity and efficacy of morphinans to the µOR. Whereas replacement of the N-methyl substituent in morphine (1) and oxymorphone (2) by an N-phenethyl group enhanced binding affinity, selectivity and agonist potency at the µOR of 1a and 2a, the N-phenethyl substitution in 14-methoxy-N-methylmorphinan-6-ones (3 and 4) turned selective µOR ligands into dual µ/δOR agonists (3a and 4a), a profile that currently emerges as a promising approach to opioid analgesic drug discovery [26][27][28][29][30][31][32] . Furthermore, we have demonstrated that the N-phenethyl substituted morphinans 1a-4a are effective and potent antinociception agents without causing unwanted motor impairment in mice after s.c. administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was not noticed for 14-OMO (3) vs. 3a, and 14-MM (4) vs. 4a, indicating that an increased µOR affinity can be achieved by either a 14-methoxy or by an N-phenethyl substitution, as key sites to be targeted in modulating the binding affinity and efficacy of morphinans to the µOR. Whereas replacement of the N-methyl substituent in morphine (1) and oxymorphone (2) by an N-phenethyl group enhanced binding affinity, selectivity and agonist potency at the µOR of 1a and 2a, the N-phenethyl substitution in 14-methoxy-N-methylmorphinan-6-ones (3 and 4) turned selective µOR ligands into dual µ/δOR agonists (3a and 4a), a profile that currently emerges as a promising approach to opioid analgesic drug discovery [26][27][28][29][30][31][32] . Furthermore, we have demonstrated that the N-phenethyl substituted morphinans 1a-4a are effective and potent antinociception agents without causing unwanted motor impairment in mice after s.c. administration.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous pharmacological and biochemical reports and studies with opioid receptor knockout mice have provided evidence on the modulatory interactions between the µOR and δOR systems [22][23][24][25][26] . While the mechanisms are still unknown, several studies have established that the therapeutic profile of opioids could be improved by simultaneous modulation of the µOR and δOR, with compounds designed to target both receptors based on peptidic structures, non-peptidic structures or utilize the morphinan scaffold [25][26][27][28][29][30][31][32] . We 13 and others 11,12 have reported that the N-phenethyl substituted morphinans 1a and 2a exhibit increased antinociceptive potencies than their respective N-methyl analogues morphine (1) and oxymorphone (2) in mouse models of acute thermal nociception after subcutaneous (s.c.) administration, which is in line with findings from binding and functional in vitro assays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These beneficial properties of the hybrids may be associated with DOP receptor activity because the effectiveness of DOP receptor ligands does not change in neuropathic pain. 33 , 40 , 42 , 70 In addition, a multimodal approach has been used in the treatment of neuropathic pain, 64 and SHU9119 causes a delay in the development of analgesic morphine tolerance, which is important for overcoming therapeutic restrictions. 26 , 59 , 62 Thus, the use of hybrids seems to be an interesting and promising direction for innovative therapies for the treatment of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] At present, no δOR-selective opioid agonists have been approved for clinical use, in part due to δOR agonists causing seizures, 15 a side effect that has been associated with β-Arr 2 recruitment. 16,17 Because of the described limitations associated with µOR-selective and δOR-selective opioids, a pharmacological strategy for treating acute and chronic pain has emerged that relies on dual activation of both the µOR and δOR, [18][19][20][21][22][23][24][25][26][27] and some of these bifunctional agonists indeed display antinociception with reduced tolerance, dependence, locomotor activation and selfadministration relative to classical morphinans. [18][19][20]27 Thus far, the development of these µOR/δOR dual agonists has largely ignored β-Arr 2 recruitment, which makes it impossible to correlate their reduced side effect profile with µOR/δOR dual agonism as opposed to β-Arr 2 recruitment.…”
mentioning
confidence: 99%